Diagnostic performance of novel inflammatory biomarkers based on ratios of laboratory indicators for nonalcoholic fatty liver disease - Zhao, Yanhua; Xia, Junxiang; He, He; Liang, Shanshan; Zhang, He; Gan, Wei (Frontiers in Endocrinology, 2022)
Introduction: There is few effective biomarkers for diagnosing nonalcoholic fatty liver disease (NAFLD) in clinical practice. This study was aimed to investigate the predictive ability of novel inflammatory biomarkers, including the monocyte to high-density lipoprotein cholesterol ratio (MHR), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR), for NAFLD. Methods: A total of 4465 outpatients diagnosed with NAFLD and 3683 healthy controls were enrolled between May 2016 and November 2021 from the West China Hospital of Sichuan University, and anthropometric and laboratory examination data were collected. The two-sample Mann-Whitney U test and binary logistic regression analysis were used to evaluate the correlations between four inflammatory biomarkers and NAFLD. The areas under the curves (AUCs) of receiver operating characteristic were used to evaluate their predictive ability for NAFLD. Results: The MHR, NLR and LMR were higher in patients with NAFLD than in healthy controls (P＜0.001), whereas the PLR was remarkably lower (P＜0.001). The OR values of the MHR, NLR, PLR, and LMR were 1.599 (1.543-1.658), 1.250 (1.186-1.317), 0.987(0.986-0.988) and 1.111(1.083-1.139), respectively(P＜0.001). After adjusting for confounding factors, MHR was still the most relevant risk factor for NAFLD compared with other inflammatory markers (P＜0.001). The AUCs of the MHR, NLR, PLR, and LMR were as follows: 0.663 (0.651-0.675), 0.524 (0.512-0.537), 0.329 (0.318-0.341), and 0.543 (0.530-0.555), respectively (P＜0.001). Furthermore, the diagnostic model combining the MHR with alanine aminotransferase, aspartate aminotransferase, total cholesterol, triglycerides, fasting blood glucose, creatinine, uric acid, and body mass index had the best AUC of 0.931 (0.925-0.936). Conclusions: MHR was superior to NLR, PLR and LMR as an inflammatory biomarker in the prediction of NAFLD. When combined with relevant laboratory parameters, the MHR may improve the clinical noninvasive diagnosis of NAFLD.